Aplikasi al-QawÃ¢âid al-FiqhÃ®yah sebagai Nalar Deduktif dalam IstinbÃ¢t Hukum Islam - Arfan, Abbas (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
This paper discusses the application of al-qawÃ¢âid al-fiqhÃ®yah (legal principles) as deductive reason in legal reasoning through usÃ»l al-fiqh approach. This paper seeks to answer a problem of how deductive reason using al-qawÃ¢âid al-fiqhÃ®yah is regarded as the source of Islamic law in the perspective of classical and contemporary religious scholars (ulama). Basing mainly on the legal approach, this paper argues that not all ulama are familiar with, and therefore, employ al-qawÃ¢âid al-fiqhÃ®yah in the making of Islamic legal opinion. This study concludes that the views of classical and contemporary âulama on this issue can be classified into three groups: a) those who categorically reject legal principles as direct reference of Islamic legal reasoning; b) those who permit the use of legal principles as evidence or reference in legal reasoning; and c) those in the middle position, permitting the use of legal principles as reference on the condition that this principle should be derived from the primary source of Islamic law (al-QurâÃ¢n and Sunnah), not from the legal thought of jurists.